PENGENALAN KONTEKS NEW MATH PEMPEK TOPIK UANG DALAM PERDAGANGAN - E.I, E.I. Pusta Siligar; Ratu, Ratu Ilma Indra Putri; Zulkardi; Hapizah (Jurnal Berdaya Mandiri, 2025)
This workshop aims to introduce a context in math learning, namely New Math Pempek, with a focus on the topic of money in trade. The choice of pempek context, as a widely known Palembang specialty, aims to present a relevant and meaningful learning experience for students. Through the making of New Math Pempek, workshop participants are invited to explore basic math concepts such as capital, selling price, and profit and loss calculation. This approach is in line with the principles of Indonesian Realistic Mathematics Education (PMRI), which emphasizes the importance of linking mathematics with real life. The workshop activities were designed to be interactive by involving discussions, contextual problem solving, and the development of student activity sheets using the context of New Math Pempek. Evaluation results show that the use of local context is able to provide the latest trend for mathematics learning with context innovation. This workshop is expected to be an inspiration for educators in designing mathematics learning that is contextual, applicable, and fun. Keyword: New Math Pempek, PMRI, Money In Trade